Acoustic Ecologies: Architecture, Nature, and Modernist Experimentation in West Berlin - Jasper, Sandra (Annals of the American Association of Geographers, 2019)
Existing geographical research on sound has largely focused on the relationship between music and place. The actual places of music—concert halls, opera houses, and other listening and performance spaces—have remained an empirical lacuna. Concert halls are influential agents over urban space. They are not only flashpoints of urban culture, they also technologically mold urban space and transform our acoustic experience of the city. In this article, I use the modern concert hall as a conceptual and empirical window on the world to examine the relationship between sound, modernity, and urban space. The Berlin Philharmonie, designed by the German architect Hans Scharoun and completed in 1963, is considered one of the most influential modern concert halls and a precursor to the currently prevalent vineyard-style design. It is suggested that Scharoun’s radically democratic spatial design is significantly different from the contemporary boosterism of iconic halls and the widening scope of a late-modern economy of experiential intensity. A close reading of Scharoun’s modernist experiments with sound in postwar Berlin highlights the underexplored theoretical and political tensions around what we might refer to as acoustic modernis